Measurement of Water Resource Efficiency and Resilience in China's Provinces and Their Co-evolutionary Analysis - JING Yanyan; ZHENG Defeng; ZHANG Xirui (Renmin Zhujiang)
Water resource efficiency and resilience are two core issues in sustainability research. Analyzing their synergistic development in China is of great significance for promoting sustainable water resource utilization across the nation. Based on the Super-Efficiency SBM model and three-dimensional vector model, this study measures the water resource efficiency and resilience levels of 30 provinces and regions in China from 2000 to 2022. Furthermore, the Haaken model is employed to explore the co-evolution characteristics of these two factors. The results show that during the study period, water resource efficiency exhibited a fluctuating pattern of increase followed by a slow decline. In 2022, the average regional water resource efficiency in China was 0.47, indicating an overall inefficient state. Over the same period, the overall water resource resilience in China demonstrated a stable fluctuation, followed by a rapid increase and then a slow increase trend. There were gradient differences in resilience levels among regions, with the eastern region > northeastern region > central region > western region. Throughout the study period, the overall co-evolution trend of water resource resilience and efficiency in China showed a fluctuating increase trend, with water resource efficiency serving as the order parameter in co-evolution, playing a positive guiding role in the evolution process of the entire system.